A comprehensive review on the application of hybrid nanofluids in solar energy collectors. (October 2021) - Xiong, Qingang; Altnji, Sam; Tayebi, Tahar; Izadi, Mohsen; Hajjar, Ahmad; Sundén, Bengt; Li, Larry K.B.
Graphical abstract: Highlights: Solar energy collectors using hybrid nanofluids have been reviewed. Non-concentrating and concentrating solar collectors are described. Hybrid nanofluids shows significant enhancement of thermal and optical performance. Stability and cost discovered to be most important limitations. Concentration of nanoparticles affects optimum values of the key parameters. Enhancement of the photo-absorption of solar energy systems has been reported. Abstract: Over the years, nanofluids have proved to be beneficial in various heat transfer applications, particularly in solar energy collectors. Hybrid nanofluids have also shown promise in such applications due to their enhanced thermal conductivity relative to mono-nanofluids and to pure fluids. The aim of this review paper is to scrutinize recent research in this topic in order to identify the key advantages and disadvantages of hybrid nanofluids as heat transfer agents in solar energy collectors. First, the various types of non-concentrating and concentrating solar collectors are described. Then, recent research on hybrid nanofluids is summarized and discussed. Most studies have reported significant enhancements in the thermal and optical performance of solar thermal energy devices operating on hybrid nanofluids. The thermal efficiency was found to be proportionally dependent on the nanoparticles' fraction in regular fluids with reasonable values. Finally, the limitations of the presented studies, relating to considerations such as stability and pumping power requirements, as well as recommendations for future investigation are addressed.